2018
DOI: 10.1111/jvim.15096
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and kinematic follow‐up gait analysis in Doberman Pinschers with cervical spondylomyelopathy treated medically and surgically

Abstract: BackgroundThe efficacy of treatment of dogs with cervical spondylomyelopathy (CSM) is commonly based on the owner's and clinician's perception of the gait, which is highly subjective and suffers from observer bias.Hypothesis/ObjectivesTo compare selected kinetic and kinematic parameters before and after treatments and to correlate the findings of gait analysis to clinical outcome.AnimalsEight Doberman Pinschers with CSM confirmed by magnetic resonsance imaging.MethodsPatients were prospectively studied and tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Currently, there are no clear evidence‐based guidelines for choosing which procedure is superior for an individual CSM patient, and the degree of stability or mobility that is ideal with distraction‐stabilisation techniques. Interpretation of the literature is difficult due to variable outcome measures among studies, and appropriate comparisons among studies do not exist …”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no clear evidence‐based guidelines for choosing which procedure is superior for an individual CSM patient, and the degree of stability or mobility that is ideal with distraction‐stabilisation techniques. Interpretation of the literature is difficult due to variable outcome measures among studies, and appropriate comparisons among studies do not exist …”
Section: Discussionmentioning
confidence: 99%
“…Neurologic status at the time of initial MRI and study enrollment was graded from 0 to 5, consistent with a previously published grading scale widely used in CSM studies: 11,27‐29 grade 0, normal neurologic examination; grade 1, cervical hyperesthesia; grade 2, mild pelvic limb ataxia or paresis with or without thoracic limb involvement; grade 3, moderate pelvic limb ataxia or paresis with thoracic limb involvement; grade 4, marked pelvic limb ataxia or paresis with thoracic limb involvement; and grade 5, nonambulatory tetraparesis. Grading was performed using a combination of video recording and retrospective assignment based on neurologic examination forms.…”
Section: Methodsmentioning
confidence: 95%
“…8 On the other hand, force plate gait analysis can objectively evaluate limb function and has been used to evaluate postoperative recovery from various orthopaedic and neurological diseases. 9,10 The clinical results of various surgical procedures for cranial cruciate ligament rupture have been reported using force plate gait analysis and pressure walkway measurement system. Some studies reported that tibial plateau levelling osteotomy was superior to extracapsular stabilization, 11,12 although other studies reported no difference when using force plate gait analysis.…”
Section: Introductionmentioning
confidence: 99%